Characterization of a Gamma Radiation (60Co) Induced Mutant Population of Prickly Pear Cactus (Opuntia velutina F.A.C. Weber) Plants In Vitro Using ISSR Molecular Markers - Eréndira Rubio-Ochoa; Eulogio De la Cruz-Torres; Rosa Elena Pérez-Sánchez; Héctor Eduardo Martínez-Flores; Liberato Portillo; Pedro Antonio García-Saucedo; Juan Florencio Gómez-Leyva (Horticulturae, 2025)
The nopal cactus, a plant from the Cactaceae family, holds significant economic and nutritional value for Mexico. This study aimed to enhance the genetic diversity and morphological traits of Opuntia velutina, a species cultivated as a vegetable nopal. A total of 1050 in vitro O. velutina explants were exposed to 15 different doses of gamma radiation from 60Co gamma, ranging from 5 to 125 Gy. The lethal dose was above 50 Gy, with an LD50 of 22.8 Gy for stimulating in vitro shoot growth. Shoots derived from doses between 5 and 50 Gy were subjected to in vitro shoot proliferation across four consecutive generations to stabilize morphological traits. Cluster analysis categorized the 178 irradiated shoots into 13 distinct morphological groups (CG1–CG13). Twenty-seven shoots exhibiting significant morphological improvements, such as a 50–100% increase in cladode length, up to a six-fold increase in shoot number, and up to a seven-fold increase in root number, were selected for molecular analysis of genetic diversity. Six primers were used with the Inter Simple Sequence Repeat (ISSR) molecular markers to examine genetic uniformity, yielding 54.5% polymorphic bands, indicating a high level of genetic variation. Both a UPGMA dendrogram and STRUCTURE-based Bayesian analysis confirmed the genetic divergence among the selected mutant lines. Overall, gamma irradiation effectively enhanced both phenotypic and genotypic diversity in O. velutina. This study corroborates that in vitro mutagenesis through gamma radiation is a viable strategy for generating novel genotypes with breeding potential within the Opuntia genus.